A Method of Constructing Non-Homogeneous Model With Weibull Distribution. Issue 3 (February 2019) - Fang, Hongliang; Hu, Jun
Abstract: When the slope is numerically simulated, the more realistic it is, the more authentic the simulation results are. How to correctly deal with the uncertainty and randomness of rock slope materials is always a difficult problem in modeling of slopes. Taking an open pit slope as an example, in order to get a more realistic slope model, through the analysis of the slope point load data of the open pit mine, it is known that the mechanical properties of the slope are in accordance with weibull distribution. Based on the weibull distribution, the volume modulus, shear modulus, cohesion and tensile strength of the slope model are randomly assigned to the slope by monte-carlo method, and the non-homogenization modeling of the slope is carried out. The modeling analysis process and method of non-homogenization modeling based on flac3d have certain reference significance to the construction of similar models.